SEAGRASS LOSSES CONCERNS: DOES SEDIMENT METAL POLLUTION MATTER? - Araujo, Clarissa Lourenço de; Loureiro, Daniel Dias; Ferreira, Marcos Manoel; Lacerda, Luiz Drude de; Fernandez, Marcos Antonio; Machado, Wilson Tadheu Valle (Geochimica Brasiliensis, 2015)
Seagrass losses result in the losing of well-known environmental services (e.g. nutrient retention), but a potential additional service loss is the trace metal retention by seagrass-colonized sediments. A preliminary study within a coastal lagoon in SE Brazil showed that upper layers of sediments colonized by the seagrass Ruppia maritima presented significantly higher reactive (HCl-extractable) concentrations of Fe, Mn, Cu and Zn than adjacent bare sediments. A lower sensitivity to R. maritima colonization was observed for Pb. Decreasing metal trapping capacity due to R. maritima removal deserves attention, since this practice occurs in the study area.